2018
DOI: 10.1186/s12886-018-0963-3
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophakic mini-monovision: high patient satisfaction, reduced spectacle dependence, and low cost

Abstract: BackgroundCataract surgery with pseudophakic mini-monovision has lower out-of-pocket patient expense than premium multifocal intraocular lenses (IOL). The purpose of this study was to evaluate patient-reported satisfaction and spectacle dependence for key activities of daily living after cataract surgery with pseudophakic mini-monovision. The study also examined statistical relationships between patient demographic variables, visual acuity and satisfaction.MethodsProspective cohort study of 56 patients (112 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 16 publications
1
29
0
3
Order By: Relevance
“…Comparison with previous studies concerned with the same trifocal IOL would not be effectively achieved 11,16,18,20,21,26. The same was concluded when revised other works not dealing with the current IOL 11,13,14,2931. There are no standards in methodology-assessing subjective perception for vision after multifocal IOL implantation, not to mention results retrieved from this assessment.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Comparison with previous studies concerned with the same trifocal IOL would not be effectively achieved 11,16,18,20,21,26. The same was concluded when revised other works not dealing with the current IOL 11,13,14,2931. There are no standards in methodology-assessing subjective perception for vision after multifocal IOL implantation, not to mention results retrieved from this assessment.…”
Section: Discussionsupporting
confidence: 52%
“…Questions vary in number and contents. Most of the studies simply represented the answers in term of percentage of 3–4 levels of satisfaction 1014,16,2931. Those which chose to use scoring, used it in a descending manner (0 being the best),18,20,21,26 or ascending (0 being the worst).11 The final score also varied from 4,20 618,21,26 and 10.11…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Previous research has shown that MIOLs or monovision techniques can provide patients with good visual acuity at various distances and spectacle freedom. [7][8][9][10] Mix-and-match of IOLs with different add powers is an approach that has been used to individualize visual correction. [11][12][13] Combinations of near add MIOLs and low add MIOLs, such as +4.0 D add and +2.75 D IOLs have shown good visual acuities for near and distance performance, however less has been reported about the combination of +2.75 D with a +3.25 D IOL.…”
Section: Introductionmentioning
confidence: 99%
“…Monovision is achieved typically by correcting the dominant eye to emmetropia for best results regarding distance visual acuity, while the nondominant eye is corrected for near visual acuity. The amount of myopia in the near eye can be varied according to the patient's needs, with targets of À0.75 to À1.00 selected for those who desire intermediate vision and less loss of distance acuity and À1.50 to À1.75 for those seeking the ability to read [63]. We do not recommend near correction more myopic than this, as it can result in significant loss of stereopsis and is often not well tolerated.…”
Section: Pseudophakic Presbyopia-correcting Approaches Monovisionmentioning
confidence: 99%
“…The advantages of monovision are spectacle independence [63] combined with less risk for optical phenomena [66], and, if not well tolerated, the ability to correct the myopia with laser corneal surgery. The disadvantages of monovision are the loss of uncorrected visual acuity in the near corrected eye and as noted above, some loss of stereopsis.…”
Section: Pseudophakic Presbyopia-correcting Approaches Monovisionmentioning
confidence: 99%